2018
DOI: 10.3345/kjp.2018.06436
|View full text |Cite
|
Sign up to set email alerts
|

The improvement of right ventricular function after adenotonsillectomy in children with obstructive sleep apnea

Abstract: Purpose Adenotonsillar hypertrophy (ATH) that causes upper airway obstruction might lead to chronic hypoxemic pulmonary vasoconstriction and right ventricular (RV) dysfunction. We aimed to evaluate whether adenotonsillectomy (T&A) in children suffering from obstructive sleep apnea (OSA) due to severe ATH could improve RV function.Methods Thirty-seven children (boy:girl=21:16; mean age, 9.52±2.20 years), who underwent T&A forsleep apnea due to ATH, were included. We analyzedthe mean pulmonary artery pressure (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Adenotonsillectomy increased the RV myocardial performance index in children with sleep apnea induced by adenotonsillar hypertrophy (Kim et al 2018). PFO closure in OSA patients did not significantly change the AHI and oxygen desaturation index but improved their quality of life and Epworth's score (Hoole et al 2017).…”
Section: Effect Of Osa Treatment On Patients' Cardiac Functionmentioning
confidence: 90%
“…Adenotonsillectomy increased the RV myocardial performance index in children with sleep apnea induced by adenotonsillar hypertrophy (Kim et al 2018). PFO closure in OSA patients did not significantly change the AHI and oxygen desaturation index but improved their quality of life and Epworth's score (Hoole et al 2017).…”
Section: Effect Of Osa Treatment On Patients' Cardiac Functionmentioning
confidence: 90%
“…4 Sub-group analysis for adenoidectomy and adenotonsillectomy, pre-and post-surgery (SMD: standardized mean difference; CI: confidence interval) which make this meta-analysis all the more important [23,[25][26][27][28][29]. Pediatric SDB attracts the sleep physicians', pediatricians', and otolaryngologists' concerns much more because of its increasing prevalence rate and its sequelae if left alone which include pediatric hypertension [30], increased risk of upper respiratory tract infection [31], failure to thrive [32], and neuropsychiatric problems such as attention deficiency [33], and other mood disorders such as depression [34,35]. Previous studies have indicated an increase in pediatric hypertension rates in patients with pediatric SDB even in non-obese pediatric groups [4,30].…”
Section: Discussionmentioning
confidence: 99%
“…Tables 1 and 2 show studies conducted over the past 20 years, each with a different research purpose and study methods. The available studies can be classified as observational studies (n.2) [16,17], retrospective studies (n.3) [18][19][20], cross-sectional studies (n.4) [21][22][23][24], comparative studies (n.2) [25,26], prospective studies (n.8) [27][28][29][30][31][32][33][34], and clinical trial (n.1) [35].…”
Section: Marangu D Et Al (2014) [24]mentioning
confidence: 99%
“…Diagnosis of adenoid/tonsillar hypertrophy was obtained using Brodsky's Scale in three studies [22][23][24] and by taking X-rays in four studies [22,30,32,35]. ENT surgery was reported as adenoidectomy [16,17,[20][21][22]25,[27][28][29][30][31][32][33]35], tonsillectomy [29,32], and A&T [16,17,[20][21][22]25,[28][29][30][31][32][33]35]. A cardiac evaluation was performed by Doppler echocardiography [16,17,22,24,[27][28][29][30] and the analysis of various cardiac parameters [16,17,25,27,…”
Section: Marangu D Et Al (2014) [24]mentioning
confidence: 99%
See 1 more Smart Citation